2017
DOI: 10.1111/ecoj.12348
|View full text |Cite
|
Sign up to set email alerts
|

Charitable Bequests and Wealth at Death

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…It is quite possible that estates are left, not to children, but to more distant relatives or indeed persons not related. A small but significant amount is left to charities (Atkinson et al 2017). All of these transfers are counted here as inter-generational transfers.…”
Section: Inheritance In the Uk: Sources And Methodsmentioning
confidence: 99%
“…It is quite possible that estates are left, not to children, but to more distant relatives or indeed persons not related. A small but significant amount is left to charities (Atkinson et al 2017). All of these transfers are counted here as inter-generational transfers.…”
Section: Inheritance In the Uk: Sources And Methodsmentioning
confidence: 99%
“…The few studies having analyzed bequests to charities have shown that typically only 3-6 percent of decedents have included a charity in their testament [51], suggesting that altruism towards family members and relatives is stronger than altruism towards non-kin. However, charitable bequests are more common among the very wealthy [52,53]. The study most closely related to ours is Smith et al [54], who analyzed a sample of 1,000 probated testaments from Vancouver, Canada, to test the predictions from Hamilton's rule [7]-that altruism should increase in genetic relatedness-and found that estate divisions are consistent with kin-based altruism.…”
Section: Introductionmentioning
confidence: 55%
“…Such gift types are not limited only to major donors. For example, Atkinson, Backus, and Micklewright () found that in the United Kingdom the median cash bequest to an individual organization was only ₤1,000. In the United States, several organizations permit gift annuities of only $1,000 or $2,000 (American Council on Gift Annuities ), and gifts of stock can be of any size.…”
Section: Limitations and Future Researchmentioning
confidence: 99%